DISIPLIN KERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN ROKAN HILIR - Ardi Wiranata; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Work discipline is the actual practice of employees of the set of rules contained in an organization, based on this it is expected that the effectiveness of employees will increase attitude and conduct discipline. Employee discipline can be enforced if the rules that have been enforced can be overcome by most employees in reality, that in an agency what if most of its employees obey all the rules that have been set, then employee discipline can already be established. The purpose of this study is to find out the work discipline of employees at the Rokan Hilir Regency Population and Civil Registry Service, To find out the factors that influence employee discipline in the Rokan Hilir Regency Population and Civil Registry Service.       This study uses a qualitative research method of data collection techniques, namely observation, Interview, literature study. The results of the study show that the performance discipline of employees at the Rokan Hilir Population and Civil Registry Service has not yet proceeded as expected, this can be seen from the stages of the interview results discipline problems of awareness and willingness, From the results of the interview it can be said that the awareness of employees in terms of the implementation of tasks has been running but has not run smoothly in line with expectations because there are still delays in completing tasks, basically employees should be on time and responsible for completing tasks assigned to each field of work. From the results of the study, researchers found factors that hinder the discipline of employee performance at the Rokan Hilir Regency Population and Civil Registry Service, namely first. One of the factors that influences the discipline of these employees is actually the leader because the leader is firm and fair. employee in acting, supervision is also very important for employees, then if supervision is lacking then things that are not right happen as it happens, namely one of them many employees go home early. Keywords : Disclipine, Work, Employee